Digital humanitarians how big data is changing the face of humanitarian response - Meier, Patrick (CRC Press, 2015)
The overflow of information generated during disasters can be as paralyzing to humanitarian response as the lack of information. Making sense of this information--Big Data--is proving an impossible challenge for traditional humanitarian organizations, which is precisely why they're turning to Digital Humanitarians. This new humanitarians mobilize online to make sense of vast volumes of data--social media and text messages; satellite and aerial imagery--in direct support of relief efforts worldwide. How? They craft ingenious crowdsourcing solutions with trail-blazing insights from artificial intelligence. This book charts the spectacular rise of Digital Humanitarians, highlighting how their humanity coupled with innovative Big Data solutions is changing humanitarian relief for forever.